2009
DOI: 10.1111/j.1600-0404.2008.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine treatment in male epilepsy patients improves pre-existing sexual dysfunction

Abstract: Oxcarbazepine was found to have beneficial effects on sexual dysfunction and to be effective and well tolerated in male patients with partial epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
(39 reference statements)
0
12
0
1
Order By: Relevance
“…Due to the natural effect of AEDs is to control the seizure symptoms of the patients, it seems that the more sedative AEDs have a greater impact on the sexual functioning than those AEDs with less sedative effects [46]. Intriguingly, some clinicians found that oxcarbazepine (a keto-derivative of carbamazepine) not only had the beneficial effects on SD, but also was effective for well control in PWE [48]. In line with this finding, Atarodi-Kashani et al reported that non-enzyme-inducing AEDs (i.e., Lamotrigine and Levetiracetam) could significantly improve the desire, orgasm, and satisfaction [30].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the natural effect of AEDs is to control the seizure symptoms of the patients, it seems that the more sedative AEDs have a greater impact on the sexual functioning than those AEDs with less sedative effects [46]. Intriguingly, some clinicians found that oxcarbazepine (a keto-derivative of carbamazepine) not only had the beneficial effects on SD, but also was effective for well control in PWE [48]. In line with this finding, Atarodi-Kashani et al reported that non-enzyme-inducing AEDs (i.e., Lamotrigine and Levetiracetam) could significantly improve the desire, orgasm, and satisfaction [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated the effects of seizures themselves and some older antiepileptic drugs (AEDs; carbamazepine [CBZ], phenobarbital [PB], phenytoin [PHT], and valproic acid [VPA]) on the reproductive and sexual function of male patients with epilepsy . There have been relatively few studies of newer AEDs (oxcarbazepine [OXC], levetiracetam [LEV], or lamotrigine [LTG]), and some of them are controversial . In this study, newly diagnosed male adult patients with epilepsy were randomized to receive OXC, LEV, or LTG monotherapy to observe the quality of semen, sexual function, and sex hormones before and after treatment, and to explore the effects of these AEDs on the reproductive and sexual functions of male adult patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] There have been relatively few studies of newer AEDs (oxcarbazepine [OXC], levetiracetam [LEV], or lamotrigine [LTG]), and some of them are controversial. 6,7 In this study, newly diagnosed male adult patients with epilepsy were randomized to receive OXC, LEV, or LTG monotherapy to observe the quality of semen, sexual function, and sex hormones before and after treatment, and to explore the effects of these AEDs on the reproductive and sexual functions of male adult patients with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…More safe therapies seem to rely on second-generation AEDs, like oxcarbazepine (OCX), gabapentin (GBP), levetiracetam (LEV) and lamotrigine (LTG). Although their influence on sexual functions in men has not been investigated extensively as yet, some improvement of sexual functioning during treatment with these drugs was noted (Husain et al 2000; Schwartz et al 2007; Luef et al 2009). …”
Section: Introductionmentioning
confidence: 99%